A Note on the Elasticity of Supply - Hicks, J. R. (Review of Economic Studies, 1934)
Journal Article A Note on the Elasticity of Supply Get access J. R. Hicks J. R. Hicks London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 1, October 1934, Pages 31–37, https://doi.org/10.2307/2967548 Published: 01 October 1934